2016
DOI: 10.1002/cam4.617
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk older smokers' perceptions, attitudes, and beliefs about lung cancer screening

Abstract: The US Preventive Services Task Force recommends that smokers aged 55–80 should be screened annually with low‐dose computed tomography (LDCT). This study identified demographics, smoking history, health risk perceptions, knowledge, and attitudes factors of older smokers (≥55 years) related to LDCT agreement. Using binary logistic regression, a predictive model of factors to explain LDCT agreement was produced. This is a cross‐sectional, national, online survey of 338 older smokers (≥55 years) with a ≥30 pack‐y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 21 publications
10
49
0
Order By: Relevance
“…This aligns with others findings as did the reasons why some participants expressed a preference for screening (early diagnosis and potential reassurance) and some did not (lung cancer diagnosis fear and low levels of perceived personal benefit) . Other studies have also found that waiting for results and hospital attendance created anxiety and were participation barriers . However, there were differences with some of the literature.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This aligns with others findings as did the reasons why some participants expressed a preference for screening (early diagnosis and potential reassurance) and some did not (lung cancer diagnosis fear and low levels of perceived personal benefit) . Other studies have also found that waiting for results and hospital attendance created anxiety and were participation barriers . However, there were differences with some of the literature.…”
Section: Discussionsupporting
confidence: 85%
“…Many participants in our study expressed keenness to be screened as this could result in finding lung cancer early and increase survival chances. This is more in line with Cataldo's findings and may relate to this study's more socioeconomically mixed sample or it is possible that as the researchers were NHS employed with study participation invitations arising from an NHS organization this may have reduced negative comments. This was mitigated through building rapport with participants, the topic guide and seeking alternative views; however, the researcher's influence cannot be discounted .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Lung cancer is the leading cause of death among cancer patients, that can be divided into non‐small‐cell lung cancer (NSCLC) and small‐cell lung cancer (SCLC). The occurrence of lung cancer is closely related to age and smoking . The standard chemotherapy regimens include platinum‐based chemotherapy (cisplatin, carboplatin) and other cytotoxic agents for lung cancer patients diagnosed at advance stage .…”
Section: Introductionmentioning
confidence: 99%